2015
DOI: 10.1007/s00705-015-2677-7
|View full text |Cite
|
Sign up to set email alerts
|

A new tobamovirus infecting tomato crops in Jordan

Abstract: In this study, we completed the whole genome sequence of a new tobamovirus isolated from tomato plants grown in greenhouses in Jordan during the spring of 2015. The 6393-nt single-stranded RNA (ssRNA) genome encodes four proteins, as do other tobamoviruses: two replication-related proteins of 126 kDa and 183 kDa, a 30-kDa movement protein (MP) and a 17.5-kDa coat protein (CP). Phylogenetic analysis showed that this virus does not group with either the tomato mosaic virus (ToMV) or the tobacco mosaic virus (TMV… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
233
0
7

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 220 publications
(246 citation statements)
references
References 19 publications
6
233
0
7
Order By: Relevance
“…Candela, which resemble the unique symptoms described above for the 'Odelia' variety. Phylogenetic analysis showed that the Jordanian isolate originated from a branch leading to TMV clade [19]. The high sequence identity between the Israeli isolate and the Jordanian tomato brown rugose fruit virus as well as the phylogenetic analysis (Fig 5) confirms that they originated from the same ancestral tobamovirus.…”
Section: Discussionmentioning
confidence: 84%
See 2 more Smart Citations
“…Candela, which resemble the unique symptoms described above for the 'Odelia' variety. Phylogenetic analysis showed that the Jordanian isolate originated from a branch leading to TMV clade [19]. The high sequence identity between the Israeli isolate and the Jordanian tomato brown rugose fruit virus as well as the phylogenetic analysis (Fig 5) confirms that they originated from the same ancestral tobamovirus.…”
Section: Discussionmentioning
confidence: 84%
“…KT383474.1) recently published from Jordan. [19]. This new tobamovirus caused mild symptoms on the leaves with strong brown rugose symptoms on fruits of S .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is also thought that ToBRFV may have emerged as a result of recombination. This is supported to some extent by an earlier analysis of the ToBRFV genome in which seven detection algorithms were used to identify a recombination event in a 314‐nucleotide segment of the Rep gene that identified tomato mottle mosaic virus (ToMMV) as the potential minor parent and the strain Ohio V of tobacco mosaic virus (TMV) as the major parent (Salem et al , ). There may also be common links of tomato varieties grown, seed source, alternate host(s) or cultivation system used, although these may vary in different locations.…”
Section: Emergence and Symptoms Of Tobrfv In Tomato Productionmentioning
confidence: 92%
“…To date, the incidence and current distribution of ToBRFV infection have been reported from Jordan (Salem et al , ), Israel (Luria et al , ), Mexico (Cambrón‐Crisantos et al , ), the USA (Chitambar, ; Ling et al , ), Germany (Menzel et al , ), Italy (Panno et al , ), Palestine (Alkowni et al , ), Turkey (Fidan et al , ) and China (Yan et al , ). Likely occurrences have also been reported but not confirmed in Chile, Ethiopia, Sudan and the Netherlands.…”
Section: Emergence and Symptoms Of Tobrfv In Tomato Productionmentioning
confidence: 99%